Understanding the reconstruction of police professionalism in the UK - Martin, Denise (Policing and society, 2022)
This article begins by exploring the development of police professionalism in the UK. It considers the drivers that have shaped the direction of police professionalism in England and Wales, including the influence of professional and institutional logics. Next, it outlines the current phase of ‘professionalism’, examining what has influenced the adoption of the current normative framework with specific reference to the PEQF and evidenced-based approaches. It will argue that attempts to re-professionalise the police have tended to be situated between ‘ideal types’ of professionalism, one which favours ‘professional trust and autonomy’ driven by professionals themselves towards a model of organisational professionalism motivated by a desire to standardise and limit occupational autonomy. Latterly, it will argue that these ‘ideal types’ used to conceptualise the changing nature of police professionalism fail to account for broader reconfigurations that shape professional identifies fully. Drawing mainly on the work of Noordegraaf [2016. Reconfiguring professional work: changing forms of professionalism in public services. Administration & Society, 48 (7), 783–810; 2020. Protective or connective professionalism? How connected professionals can (still) act as autonomous and authoritative experts. Journal of professions and organization] it is shown that there is a need to reconceptualise our understanding of professionalism to identify the range of factors influencing and reshaping professional identities.